2008
DOI: 10.1080/14622200802027248
|View full text |Cite
|
Sign up to set email alerts
|

Motives for smoking and their correlates in clients attending Stop Smoking treatment services

Abstract: This study investigated smokers' ratings of putative smoking motives and how these relate to smoking patterns, withdrawal symptoms, and short-term abstinence in clients attending smokers' clinics. Data were collected from 2,727 clients from two London Stop Smoking Services that offered behavioral support combined with pharmacotherapy. On a scale of 1 to 5, stress relief (M = 3.9), boredom relief (3.7), and enjoyment (3.6) were rated highest. Uses as an aid to concentration (2.9), for relief of withdrawal disco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
82
1
5

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(98 citation statements)
references
References 20 publications
10
82
1
5
Order By: Relevance
“…Women had higher scores on Tension Reduction/Relaxation and there were no gender differences on Addictive Smoking. This is consistent with previous research that women tend to be more likely to report smoking as a coping strategy including stress or negative affect reduction (Fidler & West, 2009;Gregor, Zvolensky, Bernstein, Marshall, & Yartz, 2007;Johnson, Stewart, Zvolensky, & Steeves, 2009;McEwen, West, & McRobbie, 2008;SanchezJohnsen, Ahluwalia, Fitzgibbon, & Spring, 2006). However, our finding that men scored higher than women in other RS contrasts with previous research.…”
Section: Discussionsupporting
confidence: 81%
“…Women had higher scores on Tension Reduction/Relaxation and there were no gender differences on Addictive Smoking. This is consistent with previous research that women tend to be more likely to report smoking as a coping strategy including stress or negative affect reduction (Fidler & West, 2009;Gregor, Zvolensky, Bernstein, Marshall, & Yartz, 2007;Johnson, Stewart, Zvolensky, & Steeves, 2009;McEwen, West, & McRobbie, 2008;SanchezJohnsen, Ahluwalia, Fitzgibbon, & Spring, 2006). However, our finding that men scored higher than women in other RS contrasts with previous research.…”
Section: Discussionsupporting
confidence: 81%
“…enjoyment) and coping (e.g. stress/boredom relief) motives as the highest rated motives for smoking (Fidler & West, 2009), related to daily cigarette consumption (McEwen, West, & McRobbie, 2008), increased levels of alcohol use (Cooper, 1994;Kuntsche et al, 2006b), heavier drinking problems (Bradizza et al, 1999;Carey & Correia, 1997;Cooper et al, 1992), and higher frequency of marijuana use among different populations (Bonn-Miller, Chabrol et al, 2005;Simons et al, 1998Simons et al, , 2000. Those findings are in line with the proposition that substance use motives could be reduced to the negative and positive reinforcement motive dimensions (Battista et al, 2008).…”
Section: Discussionsupporting
confidence: 77%
“…Results of previous research also showed that social motives were significant determinants of the current smoking status among adolescents (Amin, Amr, & Zaza, 2011;McEwen et al, 2008), and also most adolescents reported drinking for social and sometimes for enhancement motives (Kuntsche et al, 2005), while older persons were less likely to drink for social reasons (Moran & Saliba, 2012).…”
Section: Discussionmentioning
confidence: 64%
“…Although self-reported stress seems to be clearly related to reduced smoking abstinence ( Fiore et al, 2008 ), the relationship between boredom relief and relapse to smoking has been inconsistent ( McEwen, West, & McRobbie, 2008 ;Richmond et al, 2006 ), and no studies of the impact of boredomrelated smoking and cessation are noted. Future studies of intermittent and light smokers should consider these situations as Note .…”
Section: Discussionmentioning
confidence: 99%